Gilpinia fennica (Forsius, 1911) new to Poland (Hymenoptera, Symphyta: Diprionidae), and a review of the species - Borowski, Jerzy; Marczak, Dawid (Entomologica Fennica, 2015)
The paper presents information about the discovery of a new species of diprionid sawfly for the Polish forests. This is Finnish conifer sawfly Gilpinia fennica (Forsius). One female of the species was caught in a screen trap while trapping of saproxylic beetles in Kampinoski National Park. The Finnish conifer sawfly is the fifth species living on spruces in Poland. It is also one of the least observed European diprionid. Poland, after Finland, Russia, China and Sweden, is the 5th country where this species has been discovered. In addition, the paper presents information on the geographical distribution and biology of the species.